In-field superconducting critical current of Y0.5Gd0.5Ba2Cu3O7-σ films obtained by a multi-step deposition process. Issue 16 (November 2017) - Yao, Yanjie; Liu, Linfei; Wu, Xiang; Wang, Binbin; Lu, Saidan; Wang, Wei; Li, Yijie
Abstract: For most applications of high-temperature superconducting tapes, a high critical current ( I c ) and critical current density ( J c ) under a magnetic field are both required. The simplest way to achieve high I c is to increase the thickness of the superconducting layer. However, doing so also reduces J c, which is called the thickness effect. In this work, to inhibit the thickness effect, a series of Y0.5 Gd0.5 Ba2 Cu3 O7-σ (YGBCO) films with different thicknesses (240–1200 nm) were deposited by multi-step pulsed laser deposition on cerium oxide (CeO2 ) buffered substrates. The thickness dependence of the in-field J c was systematically investigated. The in-field I c at 77 K and 0–0.5 T was measured using the four-probe method, the surface morphology was observed using scanning electron microscopy, the structure and texture were measured using X-ray diffraction, and the internal residual stress was evaluated using the Williamson–Hall method. It was found that J c first increased and then decreased with increasing YGBCO film thickness. The 480-nm YGBCO film had the highest J c of 4.33 MA/cm 2 at 77 K and a self-field>1.5 MA/cm 2 under a magnetic field of 0.5 T. A 720-nm YGBCO film showed the slowest rate of J c degradation under a magnetic field. The experimental results are discussed by considering the deposition process and growth model.